A clinical review of long-COVID with a focus on the respiratory system. Issue 3 (7th May 2022) - Daines, Luke; Zheng, Bang; Pfeffer, Paul; Hurst, John R.; Sheikh, Aziz
Abstract : Purpose of review: Persistence of symptoms after acute coronavirus disease 2019 (COVID-19), often described as long- COVID, is common and debilitating. In this article, we review the epidemiology, clinical features, and research priorities for long-COVID focusing on the respiratory system. Recent findings: Breathlessness, cough and chest pain were the most commonly reported respiratory symptoms associated with long-COVID. In hospitalised patients, abnormalities on lung function testing or chest imaging were observed less commonly at 12 months compared to six months since discharge. Clinical assessment of patients with persisting symptoms after acute COVID-19 requires a comprehensive evaluation to exclude other possible causes for symptoms. With no robust current evidence for interventions to treat long-COVID respiratory symptoms, symptomatic treatment, supported self-management and pulmonary rehabilitation should be considered to help individuals with respiratory symptoms associated with long-COVID. Summary: Long-COVID is a debilitating syndrome that often includes persisting respiratory symptoms and to a lesser degree, abnormalities in lung physiology or imaging. Respiratory features of long-COVID may reduce over time, yet resolution is not seen in all cases. Future research is needed to understand the natural history of long-COVID, identify factors associated with spontaneous improvement/persistence, investigate mechanisms for persisting symptoms, and test interventions to prevent and treat long-COVID.